Energy analysis of gait in patients with down syndrome. Issue 11 (November 2022) - Ferrario, Cristina; Condoluci, Claudia; Tarabini, Marco; Galli, Manuela
Abstract: Background: the primary aim of this study is to analyse the energy parameters of patients with Down syndrome compared to a control group and secondly to verify whether the sport activity leads to differences in energy expenditure. Methods: 3 groups of subjects were identified: 8 healthy subjects and 147 subjects with Down syndrome, of whom 14 played sports at least once a week. An energy index was calculated, given by the ratio between potential and kinetic energy. Next, kinetic ad potential energy parameters were extrapolated at 60% of the gait cycle (propulsion phase). Findings: Down syndrome group was compared with the control group and emerged that the energy index was higher in the first one. No changes were found between Down syndrome and Down syndrome Sport groups. The analysis of the energy parameters showed that all parameters, except the medio-lateral kinetic energy, were higher in the control than in the Down syndrome groups. The potential energy, medio-lateral kinetic energy, and vertical were higher in the Down syndrome Sport group than in the Down syndrome group. The kinetic energy and the mean velocity were higher in the control group than in Down syndrome Sport group while the medio-lateral kinetic energy was lower. Interpretation: sport modified the parameter of potential energy but not that of kinetic energy, which continued to be different compared to the healthy group and increased the oscillations in the medio-lateral plane, which were double compared to Down syndrome group. The increase in potential energy, found to be almost equal to that of control group, indicates an increase in vertical oscillations. This could be because subjects who practise sports have stronger muscles that allow a greater push-off ability, which therefore increases their potential energy. Abstract : Energy analysis; Energy index; Down syndrome; Sport; Gait analysis.